Preparing for Life in Humanity 2.0 - Fuller, S. author. aut Link
VI, 117 p.
Keywords: Developing directly from Fuller's recent book Humanity 2.0, this is the first book to seriously consider what a 'post-' or 'trans'-' human state of being might mean for who we think we are, how we live, what we believe and what we aim to be.